The end of the timeless God - Mullins, R. T. (Oxford Studies in Analytic Theology, 2016)
What is time? -- What is eternity? -- Presentism, omniscience, and the timeless God -- Presentism, creation, and the timeless God -- Divine timelessness and four-dimensional eternalism -- The incarnation of the timeless God